Inovasi Teh Celup Herbal Daun Sirih Cina Dengan Variasi Suhu Pengeringan - Rizka Fadhillah Cahyati; Ita Fathur Romadhoni; Lilis Sulandari; Niken Purwidiani (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
Herbal Tea Bag Product Made from Chinese Betel Leaf with Combination of Lemongrass and Cardamom. This research aims to: 1) investigate the organoleptic properties of herbal tea bags made from Chinese betel leaf combined with lemongrass and cardamom, and 2) assess the sensory quality of the product through hedonic testing. This experimental study employed an observational method using a sensory evaluation panel consisting of 35 members (5 experts and 30 semi-trained panelists). Data were collected using a questionnaire. The independent variables were the proportion of Chinese betel leaf (2g, 4g, and 6g) and the addition of lemongrass and cardamom (2g) with temperature variations (40°C and 60°C) for 4 hours. The dependent variables were the sensory qualities, including shape, color, aroma, taste, and texture. The control variables included the type of materials, equipment, and processing techniques. Data analysis was performed using two-way anava and Duncan's multiple range test. The results showed that: 1) the proportion of Chinese betel leaf affected the shape and taste, 2) the drying temperature affected the color, taste, and texture, and 3) there was no interaction between the proportion of Chinese betel leaf and the addition of lemongrass and cardamom on the sensory quality of the herbal tea bags.